Exploring The Experience Of Klang Valley Youths On Fake Braces By Bogus Dentists - Hasyimah Hassan; Wan Mohamad Nasir Wan Othman; Nurul Izza Idaham (USIM Press, 2024)
The use of fake dental braces provided by bogus dentists is potentially dangerous to users' oral health. However, many people, especially youths, still fancy the use of these fake braces. This study aimed to explore the experience of youths from Klang Valley on the use of fake braces. This qualitative study used the phenomenological approach by interviewing ten youths aged between 16 - 27 years old who were from Klang Valley and wore fake braces. The tenth respondent formed the point of saturation of information in data collection. Semi-structured interviews were conducted to explore their experience in using fake braces. The interviews were conducted on the phone. Each interview lasted for a period of 10-15 minutes, and the conversations were recorded. The recordings were then transcribed verbatim, and thematic analysis of the content was used to develop the conceptual framework. Five major themes were discerned related to the respondents' views on the use of fake braces: a) physical appearance of teeth, b) influencing factors, c) seeking services of bogus dentists, d) procedures performed, and e) outcome of fake braces services. For youths with physical misalignment of teeth, fake braces are enticing due to the accessibility, availability, and affordability of bogus dentists. However, not all outcomes were perceived as favourable. Some perceived no change in the outcome, whilst most felt that fake braces led to worse consequences. This study's findings can provide the content for developing oral health promotion modules to check this unsafe practice.